The Literature of Teacher of Islamic Education at the Senior High School in Bogor City - Zulkarnain Yani (Intizar, 2018)
This paper describes the interest of reading Islamic education teachers at senior high school in the city of Bogor - West Java. This study was conducted in August - September 2016. The focus of the discussion on the urgency of reading religious literature according to Islamic education Teachers at senior high school in Bogor City and a wide selection of literature that the teachers are interested in. The targets are senior high school of Islamic education teachers that have been certified, both civil servant teachers and non-civil servant teachers. The purpose of this research is to know more deeply about reading interest through the urgency of reading religious literature according to Islamic education teachers at senior high school in Bogor City and a wide selection of literature that interest teachers and used in teaching Islamic Religious Education materials in schools. Based on the results of research, overall, interest in reading owned by Islamic education teachers in Bogor city is still very good. As many as 94% or 34 Islamic education teachers at senior high school who say the importance of reading religious literature is essential. The variety of literature that is preferred by Islamic education teachers at senior high school in Bogor more on the material Aqidah followed by the material fiqh, morals and history of Islamic civilization